Women Empowerment in Islamic Educational Institutions - Rohmah, Sakilatur; Ahmadi, Ahmadi; Amin, Iqbal (Al-Jadwa: Jurnal Studi Islam, 2025)
Women are often considered as second-class humans after men, there are many claims directed at women to overthrow them, the implication is that women often fail to develop their careers including in education. This study aims to photograph the empowerment of women to improve equality at the MI Nurul Anwar, where the study in this study includes the empowerment of women in the institution and its implications for the quality of the institution. This study uses a qualitative approach with a case study design. Data were obtained through interviews, observations, and documentation. The analysis techniques used are data condensation, data display, and drawing conclusions. This study shows that women at MI Nurul Anwar are actively involved in strategic decision making, curriculum development, and implementation of education programs. Women's empowerment has a positive impact on improving the quality of teaching, teacher work motivation, and institutional achievement. The main challenge is the lack of awareness and limited access to education. This study emphasizes the importance of women's empowerment in Islamic educational institutions to create gender equality and improve the quality of education.